Cambridge companion to the Pre-Raphaelites - Prettejohn, Elizabeth (Cambridge companions to literature, 2012)
"The group of young painters and writers who coalesced into the Pre-Raphaelite movement in the middle years of the nineteenth century became hugely influential in the development not only of literature and painting, but also more generally of art and design. Though their reputation has fluctuated over the years, their achievements are now recognised and their style enjoyed and studied widely. This volume explores the lives and works of the central figures in the group: among others, the Rossettis, William Holman Hunt, John Everett Millais, Ford Madox Brown, William Morris and Edward Burne-Jones. This is the first book to provide a general introduction to the Pre-Raphaelite movement that integrates its literary and visual art forms. The Companion explains what made the Pre-Raphaelite style unique in painting, poetry, drawing and prose"--